Psychology of music - Seashore, Carl E. (New York Dover publications, 1976)
Standard study by founder of Seashore test. Relationship between physical phenomena of sounds and our perception of them. Music as a medium, physical acoustics, auditory apparatus, sound perception, host of other topics. Includes 88 figures. "The thinking is rigorous and objective." ? Music Teacher (London).